SIKAP TOLERANSI ANTARETNIS - Susanto, Erika Feri; Kumala, Anisia (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
AbstractIndonesia is a country with diverse ethnic, ethnic and religious diversity, making Indonesia a multicultural country. This study aims to explore the relationship between the basic values of individuals with the attitude of interethnic tolerance in Indonesia. Individual basic values are defined as values that represent a person both in behavior and in acting. While tolerance can be interpreted as an attitude of mutual respect and mutual harmony in a difference between ethnicity, ethnicity and religion. The scale used in this study is the Portrait Values Questionnaire (PVQ) as a measure of individual basic values and The Tolerance Index (TI) as a measure of tolerance. This research method uses quantitative research methods. The sampling technique used was accidental sampling with respondents consisting of 79 people consisting of men and women aged 18-40 years. The results of this study indicate that there is a significant relationship between the variables of the basic value of individuals with an attitude of tolerance with a P-Value of 0.031 (P <0.05) with a Pearson Correlation value of 0.244 which indicates a significant positive relationship between the basic values of individuals with an attitude of tolerance . The higher the basic value of the individual, the higher the tolerance attitude between ethnic groups.AbstrakIndonesia merupakan salah satu negara dengan keberagaman baik suku, etnis, maupun agama, sehingga menjadikan Indonesia sebagai negara yang multikultural. Penelitian ini bertujuan untuk mencari hubungan antara nilai dasar individu dengan sikap toleransi antaretnis di Indonesia. Nilai dasar individu diartikan sebagai nilai-nilai yang mewakili seorang pribadi baik dalam berperilaku maupun bertindak. Sedangkan toleransi dapat diartikan sebagai sikap saling menghargai dan saling menciptakan harmonisasi dalam sebuah perbedaan baik suku, antaretnis maupun agama. Adapun skala yang digunakan pada penelitian ini adalah Portrait Values Questionnaire (PVQ) sebagai alat ukur nilai dasar individu dan The Tolerance Index (TI) sebagai alat ukur toleransi. Metode penelitian ini menggunakan metode penelitian kuantitatif. Adapun teknik sampling yang digunakan adalah accidental sampling dengan responden terdiri dari 79 orang terdiri dari laki-laki dan perempuan berusia 18-40 tahun. Hasil penelitian ini menunjukan bahwa adanya hubungan yang signifikan antara variabel nilai dasar individu dengan sikap toleransi dengan P-Value sebesar 0,031 (P<0,05) dengan nilai Pearson Correlation sebesar 0,244 yang menunjukan adanya hubungan positif yang signifikan antara nilai dasar individu dengan sikap toleransi. Semakin tinggi nilai dasar individu maka semakin tinggi sikap toleransi antaretnis.